Europeinization of Adult Education Policies: Theoretical reflections from the Spanish and Portuguese cases - Rosanna Maria Barros; Maria Belando-Montoro (Arizona State University, 2013)
The current processes of Europeanization of national public policies are recorded in the historical process of European construction, and to understand this process requires to pay attention to a dual perspective: the relationship between the construction of this regional bloc and the progressive development of a European mandate for education in general and for adult education and training (AET) in particular. To do this, we need to observe, first, that the educational field as a field of transnationalization, is a dynamic fluid construction between international and national dynamics, while we observe, moreover, that the concept of Europeanization designates a process among national political systems and the community political system. This article contextualizes the current role of the European Union in the expansion of the paradigm of lifelong learning. The process of Europeanization of education today takes on central importance in interpreting the diacritical new institutions and the emerging educational processes in current Spanish and Portuguese AET.